Comparison of Psychological Flexibility in Patients with Irritable Bowel Syndrome in Normal Counterparts - F Jahangiri; J Karimi; MR AminAfshari (Armaghane Danesh Bimonthly Journal, 2017)
Background & aim: Psychological flexibility is a major component of health-related behaviors and refers to ability to get in touch with the present moment and insist on behavior modification in line with personal values. The purpose of this study was to comparing psychological flexibility in patients with irritable bowel syndrome and normal control group.   Methods: In a case-control study 61 patients with irritable bowel syndrome which were referred to gastroenterologist in Boroujerd, were selected via convenience sampling and compared with normal control group in psychological flexibility. Acceptance and Action Questionnaire (AAQ), Cognitive Fusion Questionnaire (CFQ), Mindful Attention Awareness Scale (MAAS) and Meaningful Live Questionnaire (MLQ) were used as research tools. Independent t test was used for data analysis.    Results: The results showed that the difference between the two groups in terms of acceptance (p <0.006), mind-consciousness (p <0.001) and life based on internal values (p <0.006) is significant, as the band syndrome irritable bowel compared to the normal group received lower scores. In cognitive fusion (P <0.014) difference between two group was significant, so that the patient group achieved the higher scores. Both this findings mean lower psychological flexibility in individuals with irritable bowel syndrome.     Conclusions: According to this study, patients with irritable bowel syndrome had lower levels of psychological flexibility than normal group and it can effective in initiating or exacerbating their symptoms.